2019
DOI: 10.1007/s10653-019-00435-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the landfill of ashes from the smelter on the soil environment: case study from the South Poland, Europe

Abstract: The following research describes the influence of a metallurgical ash dump on both the soil environment and the atmosphere. Soil samples were collected along a line positioned on an unprotected, hazardous ash dump and extended into the adjacent, arable land. Three soil depths were sampled at 0-20-, 20-40-and 40-60-cm depth intervals, and in each sample, pseudo-total concentrations of Cd, Cr, Cu, Fe, Mn, Ni, Pb, Ti, Zn, Li, Sr and V were analyzed. Additionally, emissions of CH 4 and CO 2 were measured at each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Heavy metal concentration in soils from a waste dump may be caused by inadequate protection of the area surrounding the dump. As a result, heavy metal leaching and migration to groundwaters and surface flows might threaten the aquatic environment and plant cover (Twaróg et al 2020 ). The TCLP of CWA S/S heavy metal leachate can fulfil the quality criteria for landfill discharge (Suryawan et al 2019 ).…”
Section: The Effect Of Discharge Of Cwa Wastes On Landfillsmentioning
confidence: 99%
“…Heavy metal concentration in soils from a waste dump may be caused by inadequate protection of the area surrounding the dump. As a result, heavy metal leaching and migration to groundwaters and surface flows might threaten the aquatic environment and plant cover (Twaróg et al 2020 ). The TCLP of CWA S/S heavy metal leachate can fulfil the quality criteria for landfill discharge (Suryawan et al 2019 ).…”
Section: The Effect Of Discharge Of Cwa Wastes On Landfillsmentioning
confidence: 99%
“…[17,18]. Left unattended, industrial waste causes heavy metals to migrate to agricultural areas as a result of heavy rains, natural erosion, or microbial activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that FA physical confinement caused heavy metals to accumulate in the ground surrounding the dumpsites. A study conducted by Twaróg et al (2020) demonstrated in a landfill of ashes from a smelter in South Poland, Europe contained Cu, Cr, Pb, and Zn concentrations were elevated on the dumpsite and along its margins, with maximum concentrations of these elements being 82, 23, 1144, and 8349 mg/kg, respectively. These concentrations are usually several times higher than the background concentrations.…”
Section: Introductionmentioning
confidence: 99%